The Influence Of Transformational Leadership And Organizational Climate On The Performance Of Civil Servants In The Regional Secretariat Of Maros District - Hamid, Hendrawati (Journal of Management, 2023)
The purpose of this study was to investigate the impact of transformative leadership and organizational climate on the performance of Civil Servants (PNS) in the Secretariat of the Regional Government of Maros Regency, South Sulawesi Province. This study attempts to determine how much each influence of transformational leadership and organizational climate has on civil servant performance, as well as how much influence transformational leadership and organizational climate have on public servant performance simultaneously. The descriptive method with a quantitative approach was utilized in this study, with analysis based on the PLS-SEM SmartPLS 3.0 tool. The research population includes all government servants, and the sample includes 31 civil servants from Echelons IV, III, and II. The findings revealed that transformational leadership has a significant and strongest effect on civil servant performance, followed by organizational climate, and then the effect of transformational leadership and organizational climate both having a significant effect on civil servant performance